Intensive Farmaco- Surveillance of Interferon Alpha 2b Recombinant in Multiple Sclerosis. - Leslie Pérez Ruiz; Ana María Ramos Cedeño; José Cabrera Gómez; Nancy Echazábal Santana; Hailen Bobillo López (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2007)
Background: The interferon alpha 2b recombinant, produced in Cuba, is used in the treatment of different illnesses, such as the multiple sclerosis. For its commercialization it is needed to know its safety scope. Objective: To assess the adverse reactions of interferon alpha 2b recombinant in the treatment of multiple sclerosis. Method: During the period between 1996 and 2006, 70 clinical histories and data collection notebooks of patients included in the randomized double blind national clinical trial phase IV were revised. This trial was developed in the Clinic of Multiple Sclerosis of the Hospital "Dr. Gustavo Aldereguía Lima" in Cienfuegos. With regard to the total of manifested adverse reactions we analyzed type, length, and use of a given treatment to counteract them, intensity level (light, moderate, serious or lethal) and causality level (definitive, probable, possible, conditional or not related). Results: 53 patients out of the total presented 207 adverse reactions to interferon. The most frequent were: fever, migraine, chills, arthralgia, asthenia and myalgia, being most of them moderate collateral effects of definitive character. In 197 patients the outcome was favorable. Conclusion: The use of the interferon alpha 2b recombinant was safe in the treatment of the multiple sclerosis in these patients.